Pharmacogenetics of tuberculosis treatment toxicity and effectiveness in a large Brazilian cohort - Amorim, Gustavo; Jaworski, James; Yang, Jing; Cordeiro-Santos, Marcelo; Kritski, Afrânio L; Figueiredo, Marina C; Turner, Megan; Andrade, Bruno B; Velez Edwards, Digna R; Santos, Adalberto R; Rolla, Valeria C; Sterling, Timothy R; et al. (Pharmacogenetics and genomics, 2025)
Genetic polymorphisms have been associated with risk of antituberculosis treatment toxicity. We characterized associations with adverse events and treatment failure/recurrence among adults treated for tuberculosis in Brazil. Participants were followed in Regional Prospective Observational Research in Tuberculosis (RePORT)-Brazil. We included persons with culture-confirmed drug-susceptible pulmonary tuberculosis who started treatment between 2015 and 2019, and who were eligible for pharmacogenetics. Treatment included 2 months of isoniazid, rifampin or rifabutin, pyrazinamide, and ethambutol, then 4 months of isoniazid and rifampin or rifabutin, with 24-month follow-up. Analyses included 43 polymorphisms in 20 genes related to antituberculosis drug hepatotoxicity or pharmacokinetics. Whole exome sequencing was done in a case-control toxicity subset. Among 903 participants in multivariable genetic association analyses, NAT2 slow acetylator status was associated with increased risk of treatment-related grade 2 or greater adverse events, including hepatotoxicity. Treatment failure/recurrence was more likely among NAT2 rapid acetylators, but not statistically significant at the 5% level. A GSTM1 polymorphism (rs412543) was associated with increased risk of treatment-related adverse events, including hepatotoxicity. SLCO1B1 polymorphisms were associated with increased risk of treatment-related hepatoxicity and treatment failure/recurrence. Polymorphisms in NR1/2 were associated with decreased risk of adverse events and increased risk of failure/recurrence. In whole exome sequencing, hepatotoxicity was associated with a polymorphism in VTI1A , and the genes METTL17 and PRSS57 , but none achieved genome-wide significance. In a clinical cohort representing three regions of Brazil, NAT2 acetylator status was associated with risk for treatment-related adverse events. Additional significant polymorphisms merit investigation in larger study populations, particularly regarding risk of treatment failure/recurrence.